Green Supply Chain Management In Indian Industry (New Initiatives to Protect Environment) - Vaishy, Dr. P.C. (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
In the current scenario, there is a growing need to integrate environmentally friendly choices with research and supply chain management practices in the organization. The main goal of this study is to evaluate the latest literature on Green Supply Chain Management (GSCM), as well as to identify environmental concerns in this growing field. The study focuses on the development of the GSCM strategy, which also includes the fact that all researchers in this review focus on environmental and social sustainability in the management of operations and supply chain management. An important key that came out of this literature is green design, green management material, green marketing and distribution as well as return logistics. The purpose of this article is to review the GSCM over the past fifteen years and guidelines to help researchers, researchers and practitioners to better understand the integrated GSCM from a broader perspective. The discovery of literature shows that the broad reference range for green supply chain management (GSCM) is not adequately developed. Regulatory bodies that formulate regulations aimed at meeting social and environmental problems in order to facilitate the development of business and the economy, also suffer from its lack. Keywords: Green SCM, eco-design Green Marketing, Environment Management, Sustainable Supply Chain Management.